Convergent care research and its qualification as scientific research - Mercedes Trentini; Lygia Paim; Denise Guerreiro Vieira da Silva; Maria Angélica de Almeida Peres
ABSTRACT Objectives: to highlight the main attributes of Convergent Care Research that ratify it as a method of scientific research. Methods: it is a theoretical-reflective study on Convergent Care Research's theoretical-methodological assumptions. Development: Convergent Care Research is compatible with the Social Constructionism paradigm. Convergent Care Research projects have two approaches: practical and conceptual. The Convergent Care Research process corpus contains five phases: conception; instrumentation; scrutiny; analysis and theorizing. Final Considerations: Convergent Care Research rigor encompasses the relationship between research and care practice, and this corresponds to the convergence of these two dimensions. Due to its theoretical foundation and criteria of methodological rigor, Convergent Care Research is aligned with scientific research methods.